Academic Guidance: concept and importance - Said BENDOUIFAA (Social Sciences Journal, 2021)
Being one of the most important factors contributing to good achievement in the scientific research, Academic guidance serves to give a clear picture of everything velated to starting from pedagogical registration to the from works and conditions for submitting graduation letters. All of this is for the cake of bringing the university closer to citizens in general and holder of baccalaureate in particular. In this regard. Knowing what   academic guidance is and taking note of all the terms and concepts that has a relationship to it became an urgent necessity, nowadays by many factors: Pedagogic-Didactic- etc…And that is what we wanted to get into in this study entitled: " Academic Guidance: concept and importance " throughout addressing and enriching the following problems: what is the definition of the academic guidance? what is its importance?  what are the disadvantages that comes to the university if this type of guidance is neglected?